1974
DOI: 10.1063/1.1681153
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy of tetraphenylporphin and phthalocyanine

Abstract: The x-ray photoelectron spectra of tetraphenylporphin, phthalocyanine and their copper complexes were measured. The copper complexes show a single nitrogen 1s photoline, whereas the metal free bases give rise to a doublet nitrogen 1s photoline. The central pyrrole and aza nitrogens in the metal free bases could be identified, whereas the central and meso-bridging aza nitrogens in phthalocyanine could not be discriminated. Each of the central two protons in the metal free bases is localized on one of the centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
83
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(100 citation statements)
references
References 34 publications
14
83
1
Order By: Relevance
“…The binding energies for the "a" component were too low to match any values obtained for the poly-amino acids analyzed in this work. Indeed, according to data reported in the literature, 8 they can be attributed to nitrogen in iminic (C=N) groups, which can be found in amino acids such as arginine and histidine contained in the culture medium.…”
Section: Curve Fitting Of Detailed N1s Spectramentioning
confidence: 76%
“…The binding energies for the "a" component were too low to match any values obtained for the poly-amino acids analyzed in this work. Indeed, according to data reported in the literature, 8 they can be attributed to nitrogen in iminic (C=N) groups, which can be found in amino acids such as arginine and histidine contained in the culture medium.…”
Section: Curve Fitting Of Detailed N1s Spectramentioning
confidence: 76%
“…In addition, a small amount of metalfree porphyrins might be present. Metal-free porphyrins show a characteristic double peak structure for the N1s core level due to two chemically non equivalent nitrogen atoms: with and without H bonded to the N [17,20,21]. In summary, the N1s and Co2p spectra indicate that mainly Co-porphyrins are present and only a small part is potentially demetalised.…”
Section: Resultsmentioning
confidence: 92%
“…Small intensity differences of the two nitrogen peaks have been reported before, though the values of R were much closer to one. 32,62,65 Here, instead of the expected value near to one, the pyrrolic peak dominates over the iminic. We found that this effect can be reproduced in a systematic way, i.e., that for a series with increasing coverage (from submonolayer to multilayer) R increases as well.…”
Section: 63mentioning
confidence: 99%